2020
DOI: 10.1002/jeq2.20101
|View full text |Cite
|
Sign up to set email alerts
|

Factors driving nutrient trends in streams of the Chesapeake Bay watershed

Abstract: Despite decades of effort toward reducing nitrogen and phosphorus flux to Chesapeake Bay, water-quality and ecological responses in surface waters have been mixed. Recent research, however, provides useful insight into multiple factors complicating the understanding of nutrient trends in bay tributaries, which we review in this paper, as we approach a 2025 total maximum daily load (TMDL) management deadline. Improvements in water quality in many streams are attributable to management actions that reduced point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 137 publications
(296 reference statements)
1
69
0
Order By: Relevance
“…Our logistic regression model suggests that when using the continuous version of agriculture and when put into context with other landscape variables, the likelihood of a degraded stream condition increased 2.0% for every unit increase in agriculture in upstream watersheds. This, combined with our contingency table analysis where we found no evidence of a flow-alteration effect on stream condition in the agriculture-focused dataset, suggests that other stressors associated with agriculture (e.g., sediment (Noe et al 2020 ) and nutrients (Ator et al 2020 )) may be stronger factors affecting macroinvertebrates. Our logistic regression model also supports the importance of other variables as, in addition to the intensity of hydrologic alteration and urban development, we found several natural landscape variables (bioregion, drainage area, elevation, depth to the water table, calcium oxide lithology, % grasslands, and % wetland cover) and additional anthropogenic landscape variables (total freshwater withdrawals, % barren land cover) significant.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our logistic regression model suggests that when using the continuous version of agriculture and when put into context with other landscape variables, the likelihood of a degraded stream condition increased 2.0% for every unit increase in agriculture in upstream watersheds. This, combined with our contingency table analysis where we found no evidence of a flow-alteration effect on stream condition in the agriculture-focused dataset, suggests that other stressors associated with agriculture (e.g., sediment (Noe et al 2020 ) and nutrients (Ator et al 2020 )) may be stronger factors affecting macroinvertebrates. Our logistic regression model also supports the importance of other variables as, in addition to the intensity of hydrologic alteration and urban development, we found several natural landscape variables (bioregion, drainage area, elevation, depth to the water table, calcium oxide lithology, % grasslands, and % wetland cover) and additional anthropogenic landscape variables (total freshwater withdrawals, % barren land cover) significant.…”
Section: Discussionsupporting
confidence: 51%
“…5 ) may be more responsive to management practices because of fewer aspects of the hydrograph requiring remediating. We acknowledge that flow is one of many possible stressors and the most effective use of our results will be when they are put into context with other leading stressors for the Chesapeake Bay watershed (e.g., sediment (Noe et al 2020 ) and nutrients (Ator et al 2020 )).
Fig.
…”
Section: Discussionmentioning
confidence: 98%
“…To meet the TMDL load reduction targets, state and local governments are responsible for developing Watershed Implementation Plans (WIPs) that describe needed management practices. Coincident with these efforts, which have also included point source decreases (Ator et al 2020) and reductions in atmospheric nitrogen deposition (Eshleman et al 2013;Da et al 2018), water clarity and dissolved oxygen (DO) concentrations have improved some (Zhang et al 2018) and submerged aquatic vegetation has expanded in some regions (Gurbisz and Kemp 2014;Lefcheck et al 2018). However, progress has been slow (Boesch 2006) and currently less than half of the Bay area meets all water quality goals (Zhang et al 2018).…”
Section: Accepted Articlementioning
confidence: 99%
“…causing some estimated reductions to be overstated, according to a study published in May 2020 by US Geological Survey hydrologist Scott Ator and colleagues, which sent ripples of alarm through the scientific community (11,12). By using a model based on actual monitoring data, the researchers showed that nitrogen pollution from agriculture barely declined, if at all, between the early 1990s and early 2010s, compared with the double-digit percentage decrease predicted by the management model.…”
Section: Drastic Measuresmentioning
confidence: 99%